2014
DOI: 10.1103/physreva.90.043801
|View full text |Cite
|
Sign up to set email alerts
|

Supersolid phases of light in extended Jaynes-Cummings-Hubbard systems

Abstract: Jaynes-Cummings-Hubbard lattices provide unique properties for the study of correlated phases as they exhibit convenient state preparation and measurement, as well as "in situ" tuning of parameters. We show how to realize charge density and supersolid phases in Jaynes-Cummings-Hubbard lattices in the presence of long-range interactions. The long-range interactions are realized by the consideration of Rydberg states in coupled atom-cavity systems and the introduction of additional capacitive couplings in quantu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 72 publications
(79 reference statements)
2
17
0
Order By: Relevance
“…Outlook.-Our driven-dissipative supersolid is essentially different than other proposed driven-dissipative supersolid states in Jaynes-Cummings-Hubbard lattices [44,45], in that the latter ones are only the lattice supersolid with a broken discrete symmetry and no gapless Goldstone mode [46]. Crucially due to the genuine supersolidity and existence of the undamped gapless Goldstone mode, our proposal may have applications in precision measurements.…”
mentioning
confidence: 79%
“…Outlook.-Our driven-dissipative supersolid is essentially different than other proposed driven-dissipative supersolid states in Jaynes-Cummings-Hubbard lattices [44,45], in that the latter ones are only the lattice supersolid with a broken discrete symmetry and no gapless Goldstone mode [46]. Crucially due to the genuine supersolidity and existence of the undamped gapless Goldstone mode, our proposal may have applications in precision measurements.…”
mentioning
confidence: 79%
“…Recently, there has been considerable effort applied to the study of solid-state phenomena in Jaynes-Cummings-Hubbard (JCH) systems. These studies have predicted a superfluid-Mott insulator phase transition [1][2][3][4][5][6][7] , supersolid 8 and Bose-glass 9 phases, metamaterial properties 10 , and, in the presence of time-reversal-symmetry breaking, fractional quantum Hall states [11][12][13][14] . Almost all of these studies have focused on the case where each lattice element of the system is comprised of a two-level system interacting with a single photonic mode, resulting in the emergence of quasiparticles, referred to as polaritons.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in Ref. [31] a light supersolid in the extended JCH model on the square lattices was found by MF methods. The authors pointed out that the supersolid phase needed to be confirmed by other large scale numerical methods, as the results from the MF method are not very reliable.…”
Section: Introductionmentioning
confidence: 98%